2022
DOI: 10.1021/acs.jpcc.2c03948
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Carbide Nanocrystals from Nonthermal Plasma: Surface Chemistry and Quantum Confinement

Abstract: Silicon-carbide (SiC) nanocrystals (NCs) of controlled 2–4 nm size are produced in low-pressure nonthermal plasma from the simple alkylsilane precursor tetramethylsilane (TMS). Generating material on the slightly carbon-rich side of 50/50 Si/C, we establish a process for thermally removing residual carbon, which in turn promotes a degree of intrinsic solubility in polar solvents such as isopropanol (IPA). Using the size-dependent Tauc gap of luminescent silicon NCs (Si NCs) as a point of reference, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…As a result, it is ideal for use in electronic devices, high‐temperature applications, and radiation‐resistant materials [3]. Nowadays, it is possible to change the properties of bulk material by the modification of some features such as the size, shape, composition type, concentration of dopants, defects, and surface passivation [4–6]. Based on these facts, it is possible to create QD's with many materials for different applications, for instance, Hazem et al [7] design Nanoporous graphene quantum dots for wastewater treatment, Omar et al [8] study the electronic properties from a theoretical point of view, they found that TiO 2 quantum dots have possible gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is ideal for use in electronic devices, high‐temperature applications, and radiation‐resistant materials [3]. Nowadays, it is possible to change the properties of bulk material by the modification of some features such as the size, shape, composition type, concentration of dopants, defects, and surface passivation [4–6]. Based on these facts, it is possible to create QD's with many materials for different applications, for instance, Hazem et al [7] design Nanoporous graphene quantum dots for wastewater treatment, Omar et al [8] study the electronic properties from a theoretical point of view, they found that TiO 2 quantum dots have possible gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pringle et al (2020) synthesized different diameter sizes of C12-SiQDs (i.e., f B 3 to B8 nm), and PL-decay measurements gave values from t PL B 45 to 200 ms. 18 Similarly, Sefannaser et al (2021) also synthesized different sizes of C12-SiQDs (i.e., f B 2.8 to 7.0 nm), and the resulting PL-decay measurements were t PL B 10 to 120 ms. 72 Of the dozens of articles on R-SiQDs that the authors analyzed, their PL-decay is in the order of (ms to ms), and it is worth noting that almost all of them the quantum confinement theory. 7,[19][20][21]24,26,38,44,[73][74][75] Fig. 2c shows the relationship between the PLQYs as a function of the type of ligand attached to the SiQDs.…”
Section: A Introductionmentioning
confidence: 99%
“…72 Of the dozens of articles on R-SiQDs that the authors analyzed, their PL-decay is in the order of (μs to ms), and it is worth noting that almost all of them the quantum confinement theory. 7,19–21,24,26,38,44,73–75…”
Section: Introductionmentioning
confidence: 99%
“…A colloidal nanocrystal (NC) ink could address these issues and offer an efficient processing technique for SiC materials such as coatings and layered electronics. Recent work toward producing SiC NCs has been based on plasma synthesis . Depending on the process used, atmospheric contaminants can cause significant impurities.…”
mentioning
confidence: 99%
“…Recent work toward producing SiC NCs has been based on plasma synthesis. 10 Depending on the process used, atmospheric contaminants can cause significant impurities. Moreover, the effects of such impurities on the photoluminescence (PL) and surface chemistry of SiC NCs are still not well understood.…”
mentioning
confidence: 99%